CANCER CERVICAL WITH EVOLUTION FOR VULVAR CANCER: A CASE REPORT (CIPEEX, 2022)
VULVAR CANCER IS A RELATIVELY UNCOMMON GYNECOLOGICAL NEOPLASM THAT IS PREVALENT IN ADVANCED AGE WOMEN. THE VULVA IS THE AREA OUTSIDE THE VAGINA AND INCLUDES THE BARTHOLIN GLANDS, THE PUBIC HILL, THE CLITORIS, LARGE AND SMALL LIPS AND PERINEUM. BEING THAT THE GREAT LIPS ARE THE PREDOMINANT PLACE OF THE INSTALLATION OF THIS TYPE OF CANCER. THE DEVELOPMENT OF VULVAR CANCER IS USUALLY PRECEDED BY DISEASES SUCH AS CONDYLOMA AND SQUAMOUS DYSPLASIA, AND HPV HAS AN IMPORTANT PREVALENCE IN FAVOR OF THESE DYSPLASIAS. THE DIAGNOSIS, IN MANY CASES, IS LATE AND HAS HIGH RATES OF INAPPROPRIATE TREATMENT. THE PERCENTAGE OF TREATMENT SUCCESS IS CLOSELY RELATED TO THE EXTENT OF THE LESION AND THE TYPE OF THERAPY. IN ADDITION, ONE OF THE IMPORTANT DATA FOR THE PROGNOSIS IS THE STATE OF THE INGUINAL LYMPH NODES AND IF OTHER ADJACENT STRUCTURES HAVE BEEN CONTAMINATED. THE NEED FOR EARLY DIAGNOSIS IS EVIDENT, AVOIDING THE METASTASIS AND THE COMPLICATIONS THAT RESULT FROM IT. THE PATIENT HAD A HISTORY OF CERVICAL CANCER 2 YEARS AGO, HAVING UNDERGONE CHEMOTHERAPY AND RADIOTHERAPY. SHE STOPPED TREATMENT AND RETURNED AFTER THAT PERIOD COMPLAINING OF "BURNING" THE VULVA. THE DIAGNOSIS OF THE CASE WAS EXTEMPORANEOUS AND, SINCE THERE IS NO CURE FOR MOST OF THE OCCURRENCES, THE PATIENT WAS OFFERED PALLIATIVE TREATMENT AS AN ATTEMPT TO PROVIDE A BETTER SOCIAL WELL-BEING AND A BETTER QUALITY OF LIFE.
Keywords: Cancer of the vulva; Cervical cancer; Late diagnosis; Metastasis; HPV in favor of dysplasias.